A fatal case of disseminated intravascular coagulation and multiple systemic complications following multiple wasp stings - G. Thangarajah; P. Mayurathan (Asian Journal of Internal Medicine)
Disseminated intravascular coagulation (DIC) is a rare but severe complication of wasp envenoming, caused by systemic toxic effects. We report a case of a 50-year-old Sri Lankan man who sustained over 35 wasp stings, presenting with localised pain and swelling, along with systemic complications including DIC, rhabdomyolysis, mild acute kidney injury and liver dysfunction, notably without anaphylactic shock or bleeding manifestations. The management involved systemic corticosteroids, antihistamines, aggressive hydration and supportive care. The patient fully recovered. Clinical and laboratory parameters normalised by day 14. This case underscores the importance of early recognition, timely supportive care, and close monitoring to mitigate severe systemic complications from wasp stings to achieve favourable outcomes.